45.8k views
3 votes
Consider the following equilibrium: H2CO3+H2O = H3O+HCO3^-1. What is the correct equilibrium expression?

User Akintunde
by
5.4k points

1 Answer

4 votes

Equilibrium expression is
Keq = ([H3O+][HCO3^-])/([H2CO3])\\

Step-by-step explanation:

Equilibrium expression is denoted by Keq.

Keq is the equilibrium constant that is defined as the ratio of concentration of products to the concentration of reactants each raised to the power its stoichiometric coefficients.

Example -

aA + bB = cC + dD

So, Keq = conc of product/ conc of reactant


Keq = ([C]^c [D]^d)/([A]^a [B]^b)

So from the equation, H₂CO₃+H₂O = H₃O+HCO₃⁻¹


Keq = ([H3O^+]^1 [HCO3^-]^1)/([H2CO3]^1 [H2O]^1)

The concentration of pure solid and liquid is considered as 1. Therefore, concentration of H2O is 1.

Thus,


Keq = ([H3O+][HCO3^-])/([H2CO3])\\

Therefore, Equilibrium expression is
Keq = ([H3O+][HCO3^-])/([H2CO3])\\

User Tung Tran
by
4.3k points